2019
DOI: 10.1017/s0960258519000230
|View full text |Cite
|
Sign up to set email alerts
|

The GABA shunt pathway in germinating seeds of wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) under salt stress

Abstract: Soil salinity is one of the major abiotic stresses affecting seed germination, crop growth and productivity. In this study, seeds of three wheat (Triticum aestiveum L.) and three barley (Hordeum vulgare L.) cultivars were treated with different concentrations of NaCl to investigate the effect of salt on seed germination physiology and metabolism through the characterization of seed germination pattern, gamma-aminobutyric acid (GABA) shunt metabolite accumulation [GABA, glutamate (Glu) and alanine (Ala)] and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 64 publications
0
19
0
1
Order By: Relevance
“…It was proposed that when carbon shortage becomes a limiting factor for plant growth and development, GABA can be used as a carbon source to support the TCA cycle under salt stress [ 23 , 51 , 52 ]. Since GABA-T catalyzes GABA conversion into succinic semialdehyde in the GABA shunt, its overexpression will accelerate the metabolism of GABA and provide more carbon sources for the TCA cycle, which may not have an adverse effect on the TCA cycle in the transgenic plants [ 26 , 53 , 54 ]. In addition, it was suggested that GABA is also involved in cytosolic pH and osmotic adjustment mechanisms defending against various stresses [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that when carbon shortage becomes a limiting factor for plant growth and development, GABA can be used as a carbon source to support the TCA cycle under salt stress [ 23 , 51 , 52 ]. Since GABA-T catalyzes GABA conversion into succinic semialdehyde in the GABA shunt, its overexpression will accelerate the metabolism of GABA and provide more carbon sources for the TCA cycle, which may not have an adverse effect on the TCA cycle in the transgenic plants [ 26 , 53 , 54 ]. In addition, it was suggested that GABA is also involved in cytosolic pH and osmotic adjustment mechanisms defending against various stresses [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GABA shunt produces glutamate that enters from cytosol to the mitochondria for further catabolic activity and its biochemical interactions with other cytosolic respiratory pathways such as glycolysis and the oxidative pentose pathway remain to be resolved. The GABA shunt is a conserved pathway in eukaryotes ( Bouche and Fromm, 2004 ) and the important role it plays in respiratory metabolism during salinity exposure has been shown in barley and wheat during a range of developmental stages including seed germination, seedling growth, and in mature plants ( Al-Quraan et al, 2019 ; Che-Othman et al, 2020 ). This functional bypass of 2-oxoglutarte dehydrogenase to supply succinate to the TCA cycle may be one of many metabolic bypasses and shunts that are induced during salinity exposure to overcome salinity induced enzyme inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Salt exposure also increases two other GABA shunt metabolites, glutamate and alanine, and the activity GABA metabolism enzymes (Renault et al, 2010;Al-Quraan et al, 2019;Che-Othman et al, 2020). Because GABA production is closely connected to the abundance of glutamate, GABA synthesis plays an important role in determining glutamate abundance with GABA acting as a nitrogen storage metabolite.…”
Section: The Role Of the G-aminobutyric-acid Shunt During Salinitymentioning
confidence: 99%
“…GABA is involved in seed gemination and primary and adventitious root growth. GABA levels increase in germination of soybean, 41 oats, 42 barnyard millet, 43 adlay, 44 rice, 45 wheat, 46 , 47 barley, 48 and Chinese wild rice 49 seeds. GABA activates α-amylase gene expression and promotes seed starch degradation in a dose-dependent pattern in seed germination.…”
Section: Gaba Acts As a Signal Molecule In Plantsmentioning
confidence: 99%